2017
DOI: 10.4149/neo_2017_401
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of essential oil from Lavandula angustifolia in in vitro and ex vivo cultured liver cells

Abstract: Lavender is a commonly used herb in traditional medicine in Asia and Europe. It has been reported to be an effective medical plant in treating inflammation, depression and stress, thanks to its sedative and anxiolytic action, thrombotic, and antimicrobial properties. In the present study we investigated the protective effects of essential oil from Lavandula angustifolia (LO) against hydrogen peroxide and tert-butyl hydroperoxide -induced DNA damage. Also the effects of LO on the levels of enzymatic and non-enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Our results showed that the 24 h treatment of HaCaT cells with EOs affected TAS levels in a dose-dependent manner. These results are in accordance with previous studies [59][60][61], where essential oils increased the antioxidant effects in in vitro and in vivo systems (HepG2, IEC-6, hepatocytes of rat and mice). The results of Placha et al [62] demonstrated that lower concentrations of EOs improve the health status of animals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the 24 h treatment of HaCaT cells with EOs affected TAS levels in a dose-dependent manner. These results are in accordance with previous studies [59][60][61], where essential oils increased the antioxidant effects in in vitro and in vivo systems (HepG2, IEC-6, hepatocytes of rat and mice). The results of Placha et al [62] demonstrated that lower concentrations of EOs improve the health status of animals.…”
Section: Discussionsupporting
confidence: 93%
“…Evandri et al, (2005) observed that lavender oil had no mutagenic activity using bacterial reverse mutation assay in Escherichia coli WP2 uvrA strain and Salmonella typhimurium TA98 and TA100 strains. Also the level of DNA strand breaks induced by lavender oil in HepG2 cells and primary rat hepatocytes as indicated by comet assay was normal compared with untreated control cells (Kozics et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Lavender oil especially is employed in many economic industries: perfumery, cosmetic, pharmaceutical and in the flavoring and fragrance industry (Prashar et al, 2004). It has a broad spectrum of biological and pharmacological activities thanks to its antioxidant, anti-inflammatory, antimicrobial, sedative and anxiolytic activities and know it is used to treat stress and depression (Kozics et al, 2017). Strong antioxidant properties were demonstrated by (Kozics et al, 2017) who reported that Lavender essential oil has a protective role against mutagen-induced DNA damage by increasing the levels of enzymatic and non-enzymatic antioxidants (GPx-glutathione peroxidase, SOD-superoxide dismutase, GSH-glutathione) in human hepatoma cell line HepG2 in vitro and rat hepatocytes in ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The current study results revealed that the nanoemulsion is toxic to cancer cells. The anti-proliferative effect of licorice extract and lavender essential oil has been proven in previous studies [10,20]. When cancer cells become malignant, they produce sustained ROS, leading to tumor growth and progression [21].…”
Section: Discussionmentioning
confidence: 92%